An appraisal of the Department of Provincial and Local Government's management and coordination of Donor Assistance Programs to local government in South Africa - Dzengwa, Simphiwe (Rhodes University, Faculty of Commerce, Investec Business School, 2004)
This study is a contribution to the ongoing debate concerning the role and involvement of foreign donor entities in the processes of transforming and creating viable and sustainable municipal entities in South Africa. The discussion particularly focuses on the relationship between the donor community and the Department of Provincial and Local Government (DPLG) and how this relationship has been nurtured, coordinated and managed. The study acknowledges the challenges pertaining to local government transformation and the role and mandate assigned to the DPLG by the South African Constitution and the Presidential Coordinating Council (PCC) for it to facilitate the creation of developmental local government. In discussing this, consideration is given to capacity and resource constraints within the Department, which necessitate that it collaborates closely with other stakeholders, particularly donors, in seeking to augment its resource base and capacity. The Department's lack of capacity is further complicated by the various pieces of legislation, which have a serious bearing on how municipalities have to work - irrespective of their capacity and resources limitations. The research also focuses on how this relationship, between the DPLG and foreign aid donors working in the local government sector, is coordinated and managed. From evidence gathered and interviews conducted, the conclusion is drawn that there is much room for the DPLG to improve and strategically focus its interaction with donors as informed by its mandate and strategic priorities. Proposals, which entail development of donor management guidelines, setting up of a donor coordination unit within DPLG, the improvement of the understanding of donor work politics and modalities among DPLG officials, etc., are made.
Keywords: South Africa. Dept. of Provincial & Local Government; Local government -- South Africa; Municipal government -- South Africa; Economic assistance -- South Africa; South Africa -- Politics and government; South Africa -- Foreign relations